Uji Analisis Kadar Sulfur (S) Pupuk SP-36 PT Petrokimia Menggunakan Metode In-House dan Inovasi - Fitrani, Salsa; Fitriani, Ika Nur (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2020)
Fertilizer is an essential component in increasing food self-sufficiency in Indonesia. PT Petrokimia Gresik is one of the fourth-largest fertilizer producers in Indonesia and produces various kinds of fertilizers. One of the fertilizer is SP-36, contains sulphur and phosphate. This study investigated the sulphur (S) content in SP-36 fertilizer using the in-house and innovation method. The difference between the two methods is BaCl2; the in house method used BaCl2 powder, while the Innovation method used liquid BaCl2. Different used of BaCl2 were based on their colloid formation. This study used a UV-Vis spectrophotometer instrument to calculate the sulphur content of SP-36 fertilizer. The results obtained from the research show that the two methods tested can be used to measure the sulphur content in SP-36 fertilizer. The most accurate result was In house method. The average value of sulphur content in SP-36 fertilizer using the in house method is 4,83%, while the average value of sulphur content in SP-36 fertilizer using the innovation method is 5,22%.